2013
DOI: 10.3347/kjp.2013.51.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii Infection in Household Cats in Korea and Risk Factors

Abstract: Several epidemiological surveys have reported the prevalence of Toxoplasma gondii infection in stray cats in Korea, but little information is available on T. gondii infection in household cats. The aim of the present study was to assess the prevalence and risk factors of T. gondii infection among household cats reared in Seoul, Korea. A total of 474 blood samples were collected from clinically healthy household cats. All samples were tested using ELISA and PCR. The risk factor analysis was based on a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
2
9
1
1
Order By: Relevance
“…Higher prevalence was mostly reported in stray than in household cats, and in older than younger cats [19,23,27,28,31,32,33]. The correlation between seropositivity and increasing age of cats recorded in the presented study correspond with the results obtained by other authors [34,35,36]; however, a reverse dependence was also found [37,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Higher prevalence was mostly reported in stray than in household cats, and in older than younger cats [19,23,27,28,31,32,33]. The correlation between seropositivity and increasing age of cats recorded in the presented study correspond with the results obtained by other authors [34,35,36]; however, a reverse dependence was also found [37,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…This may be due to the deletion or mutation of the 529 bp repeat elements from the genome of the parasite that contributed to an alteration of the copy numbers for this gene (Wahab et al, 2010). The positive rate of Toxoplasma infection found in our study was higher (4.7%) than a previous report from Korea (Hong et al, 2013), which reported a prevalence of 2.1% in household cats. In our study, cat owners indicated that most of the T. gondii-positive cats were fed commercial cat food, but they had outdoor access (data not shown).…”
Section: Discussioncontrasting
confidence: 78%
“…However, other published surveys failed to detect any Toxoplasma oocysts in feces by light microscopy (Miró et al, 2004;Karatepe et al, 2008), perhaps because oocysts are shed in cat feces over relatively short periods after primary infection (median 8 days; Miró et al, 2004;Karatepe et al, 2008). Variations in feline diets could also potentially contribute to varying environmental prevalences of Toxoplasma oocysts (Lopes et al, 2008;Hong et al, 2013). Although T. gondii oocysts in cat feces are traditionally identified by their morphological characteristics on light microscopy (Foreyt, 2001), this technique is time consuming and requires specific technical skills.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, stray cats that hunt for food have a higher prevalence of T. gondii than those domesticated and fed with preserved food. In Korea, household cats from Seoul revealed a remarkably lower T. gondii seroprevalence (2.2%, 10/437) and B1 gene prevalence (2.1%, 10/474) [ 6 ], as compared to stray cats with 8.0-17.5% and 13.2-47.2%, respectively [ 3 - 5 , 7 , 8 ]. Another survey of household cats reported 0% (0/40) seroprevalence by ELISA (15.3% in stray cats in the same study) and 0% B1 gene prevalence by nested PCR (30.6% in stray cats in the same study) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%